Challenges to the delivery and utilisation of child healthcare services: a qualitative study of the experiences of nurses and caregivers in a rural district in Ghana - Felix Kwasi Nyande; Esmeralda Ricks; Margaret Williams; Sihaam Jardien-Baboo (BMC, 2024)
Abstract Background Sub-Saharan Africa has one of the poorest child health outcomes in the world. Children born in this region face significant health challenges that jeopardise their proper growth and development. Even though the utilisation of child healthcare services safeguards the health of children, the challenges encountered by nurses in the delivery of services, and caregivers in the utilisation of these services, especially in rural areas, have contributed to poor child health outcomes in this region. Aim This study explored the experiences of nurses and caregivers in respect of the nursing human resource challenges to the delivery and utilisation of child healthcare services in a rural district in Ghana. Methods Individual qualitative interviews were conducted with ten nurses, who rendered child healthcare services; nine caregivers, who regularly utilised the available child healthcare services; and seven caregivers, who were not regular users of these services. These participants were purposively selected for the study. Data were collected using individual semi-structured interview guides and analysed qualitatively using content analysis. Themes and sub-themes were generated during the data analysis. The Ghana Health Service Research Ethics Review Committee and the Nelson Mandela University's Research Ethics Committee approved the study protocol prior to data collection. Results Three main themes emerged from the data analysis. Theme One focused on the shortage of nurses, which affected the quality and availability of child healthcare services. Theme Two focused on inexperienced nurses, who struggled to cope with the demands related to the delivery of child healthcare services. Theme Three focused on the undesirable attitude displayed by nurses, which discouraged caregivers from utilising child healthcare services. Conclusion Nurses contribute significantly to the delivery of child healthcare services; hence, the inadequacies amongst nurses, in terms of staff numbers and nursing expertise, affect the quality and availability of child healthcare services. Also, caregivers' perceptions of the quality of child healthcare services are based on the treatment they receive at the hands of nurses and other healthcare workers. In this respect, the bad attitude of nurses may disincentivise caregivers in terms of their utilisation of these services, as and when needed. There is an urgent need to comprehensively address these challenges to improve child healthcare outcomes in rural areas in Ghana. Relevant authorities should decentralise training workshops for nurses in rural areas to update their skills. Additionally, health facilities should institute proper orientation and mentoring systems to assist newly recruited nurses to acquire the requisite competences for the delivery of quality family-centred care child healthcare services.